Theory and method of leadthrough of prophylaxis of deficit of vitamin for the students of general educational establishments - Shakhnenko V.I (Kharkov National Pedagogical University, 2010)
The role of vitamin is resulted in development and work of human organism and investigation of influence of his deficit. The method of leadthrough of independent diagnostics of providing of organism this vitamin is rotined. Day's norms of vitamin are resulted for adults and children. Also are facilities and method of leadthrough of prophylaxis of his deficit. There is a necessity of perfection of preparation of students to the balanced feed. It is necessary to complement the table of contents of education information about the method of leadthrough of prophylaxis of deficit of vitamin among students.